Clown e educação física: a brincadeira é séria - Miranda, Antonio Carlos Monteiro de (2011)
This study aimed to examine the construction of the clown along with the physical education in order to guide actions in the field of educational intervention. The action research (Thiollent, 2004) method was chosen, since it allows direct exchange between the researcher and the different social actors, building a process of mutual interaction to achieve common goals. Ten students of Physical Education from the State University of Maringa, in the third to the fifth years, participated in 20 meetings for training clown, which were developed in exercises and theater games, techniques of construction of the clown, as well as interventions with outlets and presentations in space professionals. It was noticed the possibility of working with clown in physical education with a view to the involvement of participants and the various intersections between these fields of knowledge, whether in the bodywork, in the view of a body is not fragmented or playfulness in the body that plays. Hence it is possible to conclude about the necessity of art in the context of clown training in critical and creative potential, to contribute to pedagogical practices that promote appropriate interventions along with physical education.